Case study: parallel Lagrangian visualization applied to natural convective flows - de la Cruz, L.M.; Garcia, I.; Godoy, V.; Ramos, E. (IEEE Parallel and Large Data Visualization and Graphics Symposium 2001, 2001)
Presents a visualization technique based on particle tracking. The technique consists in defining a set of points distributed on a closed surface and following the surface deformations as the velocity field changes in time. Deformations of the surface contain information about dynamics of the flow; in particular, it is possible to identify zones where flow stretching and foldings occur. Because the points on the surface are independent of each other, it is possible to calculate the trajectory of each point concurrently. Two parallel algorithms are studied; the first one for a shared memory Origin 2000 supercomputer and the second one for a distributed memory PC cluster. The technique is applied to a fluid moving by natural convection inside a cubic container.